2019
DOI: 10.3389/fenvs.2019.00100
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation Induced Changes in the Biochemical Composition of Aquatic Primary Producers and Their Effect on Grazers

Abstract: Changes in the biochemical composition of primary producers can alter their food quality, influencing their consumers and further propagating through the food web. Gamma (È) radiation is an environmentally important type of ionizing radiation as it can damage macromolecules such as DNA, proteins, and lipids due to its high frequency, short wavelength, and high energy photons. Here, we investigate whether short-term È-radiation changes the biochemical composition of primary producers and if radiation-induced ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Nitrogen starvation (Rehman & Anal, 2019), phosphate limitation (Yu et al, 2016), magnesium supplementation (Esakkimuthu, Krishnamurthy, Govindarajan, & Swaminathan, 2016;Goh et al, 2019), carbon source (Raeisossadati, Ahmadzadeh, McHenry, & Moheimani, 2014), iron content of the culture medium (Chandra, Amit & Ghosh, 2019), high salinity (Ji et al, 2018), and high light intensities (He, Yang, & Hu, 2018) can enhance the lipid content. Gamma radiation had a significant effect on the biochemical composition of phytoplankton, although these effects were species-specific (Golz & Bradshaw, 2019). The growth density of Chlorella pyrenoidosa mutated by 500 Gy of 60 Co irradiation increased by 53.1% (Cheng et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Nitrogen starvation (Rehman & Anal, 2019), phosphate limitation (Yu et al, 2016), magnesium supplementation (Esakkimuthu, Krishnamurthy, Govindarajan, & Swaminathan, 2016;Goh et al, 2019), carbon source (Raeisossadati, Ahmadzadeh, McHenry, & Moheimani, 2014), iron content of the culture medium (Chandra, Amit & Ghosh, 2019), high salinity (Ji et al, 2018), and high light intensities (He, Yang, & Hu, 2018) can enhance the lipid content. Gamma radiation had a significant effect on the biochemical composition of phytoplankton, although these effects were species-specific (Golz & Bradshaw, 2019). The growth density of Chlorella pyrenoidosa mutated by 500 Gy of 60 Co irradiation increased by 53.1% (Cheng et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…This enzyme can stimulate the accumulation of lipids within the cytoplasm and chloroplast, which might improve the tolerance to oxidative stress and resistance of the microalga (Garay et al 2014;Zhu et al 2016). As obtained by Golz and Bradshaw (2019), that the growth of Spirulina platensis has significantly increased at lower gamma irradiation doses (less than 500 Gy) while at higher doses, its growth was inhibited by 30 %. Although, exposing the microalgal cells to gamma irradiation might also lead to biomass loss Effect of gamma irradiation on growth and lipid productivity of green microalgae Another study by Abomohra et al (2016) revealed that even though the gamma irradiation had an adverse impact on the biomass production of Spirulina platensis, a significant rise in the carbohydrates, lipids, and pigments amounts was observed in biomass extracts, unlike the protein levels.…”
Section: Impact Of Different Gamma Irradiation Doses On the Microalgal Growthmentioning
confidence: 89%
“…Little information is available on the effect of γradiation on the physiological mechanism and biochemical composition of microalgae 10,11 . The objectives of this study were to investigate the effect of culture media composition, nutrients concentration (nitrogen, phosphorous, magnesium, and carbonate) as well as the dosage of γradiation on both algal growth and lipid parameters of microalga, Dictyochloropsis splendida…”
Section: Introductionmentioning
confidence: 99%